2009
DOI: 10.1245/s10434-008-0184-8
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Infection and Survival in Osteosarcoma Patients

Abstract: The clinical impact of postoperative deep infection on survival remains controversial in osteosarcoma patients. The authors identified 31 osteosarcoma patients that developed a deep infection within 1 year of operation between 1990 and 2003, and compared clinicopathologic characteristics of 31 patients that developed an infection with those of 316 patients that did not. For survival analysis, 62 noninfected patients matched for prognostic factors such as histologic response, tumor size, and location were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…A study of 412 patients with osteosarcoma has shown that the ten-year survival of 85% for patients with infection was significantly better compared to 62% in the non-infected group [10]. Controversially, this data could not be confirmed by another report on 31 infected patients out of a total cohort of 347 after matched control group analysis and the authors attributed positive effects of infection on survival to clinical characteristics of infected patients rather than to an anti-tumour effect of infection itself [11]. Our study did not find a significant impact of infection on survival (see Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A study of 412 patients with osteosarcoma has shown that the ten-year survival of 85% for patients with infection was significantly better compared to 62% in the non-infected group [10]. Controversially, this data could not be confirmed by another report on 31 infected patients out of a total cohort of 347 after matched control group analysis and the authors attributed positive effects of infection on survival to clinical characteristics of infected patients rather than to an anti-tumour effect of infection itself [11]. Our study did not find a significant impact of infection on survival (see Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Significance between survival functions was identified by the log-rank test. According to previous reports investigating the prognostic value of post-operative infection on survival [10,11], landmark analysis was performed additionally in order to better control confounding factors. For this, a landmark was defined at 12 months postoperatively and patients dying from metastases before this landmark as well as patients developing infection after this landmark were excluded before survival analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several historical and recent reports suggesting a link between improved survival and local infection in patients treated with surgery for sarcomas [23]. However, there have also been several more recent reports of retrospective data refuting this claim and it appears that conclusive data is still lacking on this question [24]. The possibility that a local infection may incite an immune response that in turn suppresses tumor cell activity is an enticing prospect.…”
Section: Discussionmentioning
confidence: 99%
“…58 Interestingly there are reports, which suggest increased survival in patients with osteosarcoma and developing periprosthetic infection after reconstructive surgery, suggesting a potential immunologic antineoplastic advantage induced by infection. 57,59 Treatment is similar to treatment of infected total knee or hip prosthesis, except there is a dramatically larger dead or infected tissue, and immune deficiency due to oncologic treatments, requiring more aggressive treatment. 60 Deep infections in patients with megaprostheses require treatment by surgical methods because the long-term administration of antibiotics alone is not sufficient.…”
Section: Custom-made Megaprosthesismentioning
confidence: 99%